2016
DOI: 10.18632/oncotarget.13694
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum pre-albumin as an independent prognostic indicator in patients with localized upper tract urothelial carcinoma after radical nephroureterectomy

Abstract: PurposeTo investigate the prognostic value of preoperative pre-albumin and albumin level in patients with localized upper tract urothelial carcinoma (UTUC) undergoing radical nephroureterectomy.Methods and MaterialsBetween January 2003 and June 2013, we evaluated data on 425 patients with nonmetastatic UTUC (Ta-4N0/+M0) who underwent radical nephroureterectomy at our institution. Low pre-albumin level was defined as <20 mg/dl, while hypoalbuminemia was defined as albumin <35 g/L. The associations of preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…Across most surgical specialties, low serum levels of albumin and prealbumin are related to severe complications, such as nosocomial infections, unplanned reoperation, gastrointestinal anastomotic leak, positive oncologic resection margins, advanced tumor stage, postoperative cancer recurrence, prolonged hospital and intensive care unit length of stay, wound complications, renal failure, gastrointestinal dysfunction, postoperative edema, and death (See Table ) …”
Section: Serum Levels Of Albumin and Prealbumin In Preoperative Risk mentioning
confidence: 99%
“…Across most surgical specialties, low serum levels of albumin and prealbumin are related to severe complications, such as nosocomial infections, unplanned reoperation, gastrointestinal anastomotic leak, positive oncologic resection margins, advanced tumor stage, postoperative cancer recurrence, prolonged hospital and intensive care unit length of stay, wound complications, renal failure, gastrointestinal dysfunction, postoperative edema, and death (See Table ) …”
Section: Serum Levels Of Albumin and Prealbumin In Preoperative Risk mentioning
confidence: 99%
“…Several studies have reported on the association of hypoalbuminemia with poor prognosis in patients with UC ( Table 5) (49,68,72,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The cutoff value of albumin varies from 2 to 4 mg/L, although it is normally around 3.5 mg/L.…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
“… 14 , 15 Moreover, Alb and pre-Alb were observed to be significantly lower in cancer individuals in comparison with the healthy controls. 16 , 17 Hence, we hypothesized that the two new biomarkers, Alb-to-Fib ratio (AFR) and Fib-to-pre-Alb ratio (FPR), might reflect the severity of systemic inflammation and predict the survival of CRC individuals.…”
Section: Introductionmentioning
confidence: 99%